1996
DOI: 10.1002/eji.1830260326
|View full text |Cite
|
Sign up to set email alerts
|

Natural killer clones recognize specific soluble HLA class I molecules

Abstract: Enhancement of major histocompatibility complex (MHC) class I expression leads to protection from natural killer (NK) cell recognition in several systems. MHC class I gene products are released from the cell surface and can be found in sera as soluble forms. To investigate the possible immunoregulatory role of soluble HLA (sHLA) in NK cell-target recognition, several sHLA antigens were studied for their ability to induce NK cell cytotoxicity modulation. NK cell-target recognition was inhibited by the addition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 52 publications
(27 reference statements)
0
21
0
1
Order By: Relevance
“…Several mechanisms have been suggested for production of sHLA, including shedding, differential splicing of mRNA [5] and proteolytic cleavage of membrane-bound HLA class I molecules [6,7]. Experiments have shown that in vitro, sHLA molecules can function as immune regulators, inducing apoptosis of alloreactive T cells [8][9][10][11] and that natural killer cells are downregulated by sHLA-I [12], but the biological functions of circulating sHLA in humans remain unknown.…”
Section: Introductionmentioning
confidence: 98%
“…Several mechanisms have been suggested for production of sHLA, including shedding, differential splicing of mRNA [5] and proteolytic cleavage of membrane-bound HLA class I molecules [6,7]. Experiments have shown that in vitro, sHLA molecules can function as immune regulators, inducing apoptosis of alloreactive T cells [8][9][10][11] and that natural killer cells are downregulated by sHLA-I [12], but the biological functions of circulating sHLA in humans remain unknown.…”
Section: Introductionmentioning
confidence: 98%
“…[14][15][16] However, we and others reported that sHLA-I molecules lead to activation-induced apoptosis, in vitro, mediated by synthesis and secretion of FasL and the consequent interaction with Fas expressed by allogeneic and autologous T and natural killer (NK) cells. [17][18][19][20][21] Furthermore, nanomolar concentrations of sHLA-I can prevent both alloreactive clones and primary T-cell cultures from recognizing and lysing their targets. 20 It has been reported that sHLA-I molecules bind to CD8 receptors expressed on cytotoxic effector lymphocytes, that is T and NK cells.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16] sHLA-I serum levels vary among different individuals and are significantly affected by inflammatory diseases and transplant rejection. [16][17][18][19] sHLA-I has been shown to inhibit cytolytic activity of both alloreactive CTL and NK cells in vitro. [13][14][15][16][17] More recently, it has been reported that sHLA-I, interacting with CD8 molecules, induces apoptosis of CD8 ϩ T lymphocytes on binding of soluble Fas ligand (FasL) to Fas antigen expressed by these cells.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon may play a role in the regulation of antigen-specific immune responses by inducing programmed cell death of effector T lymphocytes. [13][14][15][16][18][19][20][21][22][23][24] However, it is not clear whether sHLA-I delivers an apoptotic signal by interacting with CD8 only or through the simultaneous engagement of CD8 and TCR.…”
Section: Introductionmentioning
confidence: 99%